Evaluation of Effectiveness and Adverse Effects of Retraction Cord vs Retraction Paste: A Systematic Review - Bennani, V.; Chuang, Y.S.; Aarts, J.M.; Brunton, Paul (2021)
Aim and objective: The practitioner's assumptions with regards to the ideal gingival retraction technique are not well supported in the literature and contradictions still exist. Therefore, the objective of this review is to determine the effectiveness and adverse effects, of using a retraction cord compared with a retraction paste. Materials and methods: The "Preferred reporting items for systematic review and meta-analysis protocols" (PRISMA-P) 2015 guidelines were followed. Studies, published between 2010 and 2020, involving retraction cords and retraction pastes were searched for in multiple databases. Inclusion and exclusion criteria were applied and the studies were evaluated using the GRADE system. The studies were analyzed and the quantity of gingival retraction and periodontal health are reported. Results: Of the selected 10 studies, nine were randomized, and one was quasi-randomized. Five studies compared the horizontal displacement of retraction cords and retraction pastes. Eight studies described the influence of retraction materials on periodontal health. Seven studies recorded Bleeding Index (BI) scores, with five studies finding higher BI value following removal of retraction cords. According to the GRADE scoring system, the quality of research was ranked from +1 to +3 with the majority of the studies being in the +2 range. Conclusion: Astringents used with retraction cords can achieve wider and longer gingival displacement. Retraction pastes can avoid disrupting the junctional epithelium attachment and damaging the supracrestal tissue height, and produce less gingival inflammation due to the lower application forces.